Metallographic Properties of Yamato Iron Meteorite, Yamato-75031, and Stony-Iron Meteorite, Yamato-74044 - Fisher, R.M.; Spangler, C.E. Jr.; Nagata, T. (1978)
P(論文) Chemical and metallographic examination of Yamato iron meteorite, Yamato-75031,has revealed that the major elements in the iron base are 15.3% Ni, 1% P, and 0.76% Co. Very large Fe-Ni phosphides (schreibersite) are enveloped with swathing kamacite and very fine phosphides are also encased in Widmanstatten kamacite plates within a plessite matrix. The composition and microstructure are quite similar to Pinon which is classified as an anomalous high nickel ataxite. Some annealing of the plessite occurred during entry into the earth's atmosphere. Chemical and metallographic examination of Yamato stony-iron meteorite, Yamato-74044,has revealed that the major elements in the metal phase are 11% Ni, 0.1% P, 0.75% Co with adjacent pools of manganese-rich olivine veined with iron sulphide. The olivine component and the nickel content classify this stony iron as a pallasite. The nickel contents of the taenite and plessite indicate chemical equilibrium during cooling to 400℃. These samples, along with Yamato-75105,weighing from 20-60 grams, are smaller than any other iron or stony-iron meteorites. departmental bulletin paper